Efektifitas Penerapan Manajemen Strategik di SMA Muhammadiyah Cilegon dalam Meningkatkan Mutu Pendidikan - Faizal Djabidi (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2018)
Muhammadiyah High School seeks to implement Strategic Management in improving the quality of education even though in its implementation it is faced with many problems such as 1) Non-marketable school location is difficult to reach by Prospective New Students and Educational Customers (Trustees of Students) because it is located in the midst of a residential neighborhood and close with the train station, 2) Wrong views and assessments of the Muhammadiyah Organization as Ism or Religious Understanding, 3) Recruitment of Educators not from Internal or Muhammadiyah Cadres so that they do not fully understand the Muhammadiyah's ghiroh and marwah, 4) Establishment of equivalent schools (SMK Muahammadiyah) in one union, Muhammadiyah Cilegon. In this study, the authors used a Qualitative Descriptive method aimed to find out about the real picture related to the problems and strategies used in improving the quality of education. The results of the study obtained information about the effectiveness of the implementation of Strategic management in the field, namely: 1) Consistency of Muhammadiyah Cilegon High School in creating graduates who have the right to continue to Higher Education are also able to enter the world of Business and Industry (the World of Work), Professional Teachers and Education and maximize their strengths by schools, Applying the functions of School Management Information Systems, improving the quality of Education and educating the life of the Nation, 2) Having a Code of Conduct structured in improving quality in the fields of Curriculum, Student, Facilities and Infrastructure including Process Input and Output Education towards quality and competitive schools, 3) Muhammadiyah High School has a strategy in improving the quality of education and rejecting negative issues by promoting Tabayyun, discussion, holding seminars and general stadiums, education workshops, Darul Arqom debriefing and cadre of Muhammadiyah and educators. Special Principal (DIKSUSPALA)